The Ukrainian folk social daily song: the understanding of the new social roles (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is about the features of people’s understanding of the new social roles of a person according to historical and psychological factors of its being. This is most turn out in the social folklore, especially in a lyrical song. The social folklore is a separate layer of the oral traditional culture, which unites a large number of works and reflects the results of the people’s thinking of the various phenomenons, events or circumstances of the social life, offers a holistic that is generalized with typical attitude towards them.Traditionally, works in this direction associated with a reflection of the social problems, however, a deep analysis of their content leads to the conclusion that quite often they contain the results of the philosophical understanding of the problems of the existence of man, his place in the world, claiming the superiority of the spiritual values over the material, a freedom of the choice, the idea of the building a harmonious society in which each person is able to realize their abilities and needs. The texts of the Cossack, recruiting and soldier`s songs became the object of the study, represent the transformation of the social norms, behaviors, ethical and aesthetic principles, which have become the logical result of the historical, political and psychological shifts.The results of the reconstruction of the mental and emotional conditions of the person in the process of the implementing new social roles which are reflected in lyric songs  of the social orientation that indicate the transfer of its aesthetic estimates from the heroic to the tragic plane.
Keywords: people; Ukrainian social song; social role